Geology of Labuan Bajo Area, East Nusa Tenggara: A short geological note as a supplemental information to Komodo National Park - Purba, Junida R; Darman, Herman (Ikatan Ahli Geologi Indonesia, 2025)
Labuan Bajo is a captivating destination in the Lesser Sunda Islands, Eastern Indonesia. The location is renowned for its unique landscape–where volcanic remnants dramatically meet the ocean. The Komodo Dragon is the most famous animal living in the area. While the region's geological history undoubtedly encompasses a series of complex events, its regional geology has received little of the attention it deserves. This paper explores the geology of Labuan Bajo: the diverse rock formations, which consist of volcanic and carbonate sediments.The oldest rock encountered in the area is the Miocene volcanic rocks. Quaternary volcanics, which is the youngest unit, dominated the area. Columnar joints occur in some areas, indicating lava activities. Mio-Pliocene carbonates are common in the area. A cave system developed in the carbonate unit and the erosion processes develop unique shapes.